2012
DOI: 10.7763/ijbbb.2012.v2.73
|View full text |Cite
|
Sign up to set email alerts
|

Study on Carbon Distribution at Protein Regions of Disorder

Abstract: Abstract-Hydrophobic interaction is the dominant force in proteins that arises due to carbon. The content and distribution of this carbon make a protein to fold in some form to have a specific function. Diseased proteins are expectedly differing from this carbon distribution pattern. This is taken as focus of this work by taking neurodegenerative protein, the SOD for study. The carbon distribution analysis program is able to identify the disordered region clearly. A long stretch of hydrophilic/hydrophobic regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
1
8
0
Order By: Relevance
“…Mutation sites for brazzein mutants with increase in sweetness mainly at residues 29, 31 and 41 had the normal distribution curve of the carbon content with highly increased carbon frequency peak compared to the wild-type, consequently stabilized the protein and maintained it functionality. The other mutant such as E41Q maintained carbon content value at 0.314, the known value for a stable protein and being in agreement with established findings that a stable and ordered proteins have a normal distribution of its carbon content symmetrical to about 0.314 [14,16].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Mutation sites for brazzein mutants with increase in sweetness mainly at residues 29, 31 and 41 had the normal distribution curve of the carbon content with highly increased carbon frequency peak compared to the wild-type, consequently stabilized the protein and maintained it functionality. The other mutant such as E41Q maintained carbon content value at 0.314, the known value for a stable protein and being in agreement with established findings that a stable and ordered proteins have a normal distribution of its carbon content symmetrical to about 0.314 [14,16].…”
Section: Discussionsupporting
confidence: 71%
“…These mutants at residue position 30, 33 and 36 were characterized by broadened distribution curve for carbon content with decreased carbon frequency peak thus destabilized protein function in terms of its sweetness. Broadened carbon distribution curve with decreased frequency peak destabilizes the structure and possibly leading to loss of protein functionality [12,14]. Based on carbon distribution analysis on several numbers of proteins, it has previously been reported that at mutation site, a single mutation can alter the protein function [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disease proteins are expectedly differing from this carbon distribution profile. 6,7 The disorders are mainly due to carbon role in different phenomena may be of evolutionary reason. Toxicity also depends on this factor of carbon role.…”
Section: Introductionmentioning
confidence: 99%
“…When there is inadequate carbon point of distribution where alteration can be performed by probe binding at the adjacent site effectively. Accordingly initiatives are done to probe the role of carbon in dealing with other situations like, pattern recognition, 7,8 disorders in protein, 9,10 disease causing 11,12 and mutational role [11][12][13][14][15] when other forces fail to capture the essence of it. When in need one can probe those devisable mechanisms for possible arrangements to continue with carbon value based method of alternative design and action actually taken here.…”
Section: Introductionmentioning
confidence: 99%